2019
DOI: 10.1093/sleep/zsz141
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sex and body weight on lung volumes during sleep

Abstract: Study Objectives Low lung volumes are thought to contribute to obstructive sleep apnea (OSA). OSA is worse in the supine versus lateral body position, men versus women, obese versus normal-weight (NW) individuals and REM versus NREM sleep. All of these conditions may be associated with low lung volumes. The aim was to measure FRC during wake, NREM, and REM in NW and overweight (OW) men and women while in the supine and lateral body positions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Previous studies have suggested that pediatric hypertension increases along with childhood obesity, 16 and that hypertension further contributes to the clustering of obesity-related cardio-metabolic risk factors. 17 Moreover, obesity increases fat accumulation in the parapharyngeal space 18 and reduces lung volume, 19 which can also cause or aggravate OSA. Notably, pediatric OSA, obesity, and hypertension are likely to persist into adulthood and then further increase the risks of cardiovascular diseases and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that pediatric hypertension increases along with childhood obesity, 16 and that hypertension further contributes to the clustering of obesity-related cardio-metabolic risk factors. 17 Moreover, obesity increases fat accumulation in the parapharyngeal space 18 and reduces lung volume, 19 which can also cause or aggravate OSA. Notably, pediatric OSA, obesity, and hypertension are likely to persist into adulthood and then further increase the risks of cardiovascular diseases and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The likelihood of developing EFL T is markedly increased by postural change when EELV falls [ 5 , 6 ]. Lung volume falls further in a state-dependent fashion with the onset of sleep [ 7 , 8 ], but to date, we lack data about how this impacts EFL T .…”
Section: Introductionmentioning
confidence: 99%
“…10 Movement of the hyoid and laryngeal apparatus will also alter the resting lengths of attached muscles, such as the sternohyoid and sternothyroid muscles, and may reduce muscle effectiveness under some conditions, such as lower lung volumes. 11 Body position influences lung volume in both awake 12 and sleeping 13 individuals. In awake individuals the postural changes in lung volume are less in obese than in healthy weight individuals.…”
mentioning
confidence: 99%
“…12 In supine nonrapid eye movement sleep, lung volumes can fall to approximately 60% predicted in healthy weight individuals, with even greater reductions in overweight individuals. 13 Sleeping subjects with OSA, who are obese and supine, are likely to have even lower lung volumes, with displacement of the hyoid cranially. This suggests the lung volume at which ACS occurs may be important in determining its efficacy.…”
mentioning
confidence: 99%